Use of integrative and complementary practices and the quality of life of undergraduate nursing students - Gabrielli Sousa dos Santos; Marcella Cecílio de Almeida; Raquel Valente de Souza; Joyce Assunção Barros; Adriana Cristina Nicolussi (Rev Rene)
Objective: to evaluate the use of integrative and complementary practices and their association with the quality of life of nursing students. Methods: a cross-sectional study conducted with nursing students. A sociodemographic/clinical-therapeutic questionnaire and the WHOQOL-Bref instrument were used. The data were analyzed using descriptive statistics, with Levene's Test used to assess the Equality of Variances and the Student's t-test applied to compare the mean scores of the quality of life domains between the groups. Results: 73 students participated; among them, those who engaged in integrative and complementary practices reported improvements from their use and expressed a willingness to recommend them to others. The most used therapies were homeopathy, flower essence therapy, meditation, yoga, music therapy, and reiki. Regarding quality of life, when comparing the groups, students who engaged in integrative practices had higher mean scores in all domains compared to those who did not. Conclusion: few undergraduate students were familiar with and made use of integrative and complementary practices, and the quality of life of those who engaged in these practices was better compared to those who did not. Contributions to practice: the results may provide insights for strengthening the benefits of using integrative practices in this academic context.